Strategies used by nursing technicians to face the occupational suffering in an emergency unit - Alessandra Bassalobre Garcia; Maria do Carmo Fernandez Lourenço Haddad; Mara Solange Gomes Dellaroza; Fernanda Ludmilla Rossi Rocha; Paloma de Souza Cavalcante Pissinati (Rev Rene)
Objective: to understand the strategies used by nursing technicians in order to face the occupational suffering in an emergency room. Methods: qualitative study carried out in an emergency room of a high complexity hospital located in the north of Paraná state. Data were collected through semi-structured interviews with 12 nursing technicians. The analysis relied on content analysis procedures. Results: respondents revealed as individual strategies to face suffering: try not to get involved with the patient; separation between professional and personal life; and spirituality/religion as support for coping. The collective strategies described by respondents included: action planning for unexpected events in this unit; creating a supportive environment; and attempt to obtain recognition of headship. Conclusion: individual and collective strategies were used consciously by workers and should be encouraged by managers to face the occupational suffering.